Sports training and its relationship with the quality of performance in the management of sports institutions in Iraq - Mohaisen, Hasan Ali; Al-Momen, Husam Saeed (Sulaimani Journal for Humanities, 2026)
Today, having capable human resources with high quality performance, as the most important asset, is a link in the success of organizations in competitive areas. Therefore, smart managers are always trying to create conditions in the organization that not only employees use their existing capabilities, but also to develop their capabilities and improve the quality of their performance. Due to the importance of the subject of this study, a descriptive survey study was conducted to investigate sports training and its relationship with the quality of performance in the management of sports institutions in Iraq. The statistical population is the research staff of the management of sports institutions and sports clubs in Iraq, which was selected as a sample based on a simple random sampling of 300 people. A standard questionnaire was used to collect data. Cronbach's alpha coefficient of the whole questionnaire was estimated to be 0.89. Inferential statistics, Human Whitney, were used to analyze the data. The results showed that the average of tasks, job discipline, adherence to moral values and interpersonal relationships of male employees in the athlete group was significantly higher than the non-athlete group. However, there was no significant difference between female athletes and non-athletes in how to perform tasks, job discipline, how to deal with the client, personal development, interpersonal relationships and organizational behavior of employees, but in terms of adherence to ethical values, the average score of female athletes significantly. More than non-athlete. Therefore, according to the results obtained by sports officials at the University of Tabriz, it is suggested to pay more attention to staff sports and allocate more appropriate times for staff sports and to hold public sports programs to promote staff vitality and vitality.
Keywords: Sports Training; Performance Quality; Management; Sports Organizations; Iraq